Infidels and Empires in a New World Order Early Modern Spanish Contributions to International Legal Thought - Lantigua, David M. 1981- (New York Cambridge University Press, 2020)
Examines early modern Spanish contributions to international relations by focusing on ambivalence of natural rights in European colonial expansion to the Americas.
Cover -- Half-title page -- Series page -- Title page -- Copyright page -- Dedication -- Contents -- List of Figures -- Acknowledgments -- 1 Introduction: International Relations Beyond Westphalia -- Theology and the Universal Church -- International Relations, Westphalia, and Anarchy -- Valladolid and Infidels in a New World Order -- Part I The New World Crucible of Infidel Rights -- 2 Theocratic World Order and Religious Wars -- Crusades and the Rights of Infidels -- Papalist World Order Under Iberian Rule -- Taking Possession of the Indies -- Religious Wars Against Idolatry -- 3 Spanish Dominicans and the "Affair of the Indies" -- Initial Theological Debates About Conquest -- Infidel Rights, Restitution, and World Order -- Unjust War and the Ethic of Evangelization -- 4 The Politics of Natural Law at Valladolid, 1550-1551 -- Bishop Las Casas and the Valladolid Junta -- Dispossessing Idolaters -- The Imperial Politics of Natural Law -- Part II God, Empires, and International Society -- 5 From Infidels to Savages: Empires of Commerce and Natural Rights -- Christian Commerce by Force of Arms -- Individual Punishment in the State of Nature -- European Civilization and Land Ownership -- 6 The Scholastic Law of Nations, Native Occupation, and Human Solidarity -- The Spanish Scholastic-Juristic Law of Nations -- Political Agency and Consent in the Indies -- The Native Right of Resistance -- Lawful Occupation and the Christian Ethic of Intervention -- Conclusion -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Casas, Bartolomé de las -- 1484-1566 -- Influence; Indigenous peoples (International law) -- History -- 16th century; Indians -- Legal status, laws, etc -- History -- 16th century; International Law -- Spain -- History -- 16th century; Casas, Bartolome de las,-1484-1566-Influence; Electronic books